Alternative Forms of Tourism in Mountain Tourism Destination: A Case Study of Bjelašnica (Bosnia and Herzegovina) - Tvrtko Opačić, Vuk; Banda, Amra (Geographica Pannonica, 2018)
For better development of alternative tourism supply in mountain tourism destinations it is necessary to identify and evaluate tourism attractions that could be better valorised when creating tourism products. It is an essential part of the destination analysis to determine perception of local population and tourists when evaluating tourism attractiveness. Olympic Mountain Bjelašnica in Bosnia and Herzegovina is a representative case study of mountain tourism destination, whose recent phase of tourism development is characterized by a variety of tourism supply that allows practicing many forms of tourism with the dominance of the winter tourist season and the skiing tourism of mass character. The principal aim of the study is to determine the differences in the evaluation of tourism attractions of alternative tourism in tourism supply of Bjelašnica within and between group of local residents and tourists. Direct survey was conducted during the summer 2016 and sample included 98 local residents and 111 tourists. Results show: a) tourists evaluate most of attractions higher then local residents, b) some attractions are higher evaluated by younger and more educated local residents, c) older tourists evaluate cultural and historical heritage better, while tourists with college degree are most satisfied with tourism and recreational infrastructure considering the age, gender and level of education, and d) all clusters of attractions are rated as more attractive by tourists who stay at purpose-built mountain tourist resort Babin Do, compared to those in Bjelašnica’s villages. Results can be applied as a guideline to raise local residents’ awareness of tourism attractions and developing more specific tourism supply that will address not solely mass tourism, but also alternative forms of tourism.